Pembinaan Akhlak Keluarga Remaja Melalui Pendidikan Agama Islam - Rohman, Miftakhul; Basid Al Haris, Mohammad; Erly Ananta, Pinka; Darun Naja, Anang (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2023)
The current moral crisis has an impact on everyone, both in villages and marginalized communities. The reason is, the moral damage that befell the younger generation makes them worry about peace for themselves and others. When many people in the city are harmed by their actions, the condition of society is shaken to the point that self-destructive behavior occurs. In a situation like this, the country will become increasingly decline over time and become full of bad deeds. The life values ​​that the younger generation need to learn are not only customs and behavioral traditions, but also various kinds of values, including universal religious values. Teenagers and their developmental activities learn and shape their behavior to conform to the expectations of the people around them, without must be directed, supervised, forced or threatened with punishment, as in my childhood, you can definitely do those things. For teenagers, parental attention is very important. Even at a young age, religion and strong beliefs have a strong influence on their decisions. Human character and behavior play an important role in a child's family. Controlling their behavior cannot be done haphazardly without understand the development of his thinking. Good moral education must be provided.